Awareness and importance of investment among student Halal Management in UiTM Puncak Alam / Nurnadzifa Aminahar - Aminahar, Nurnadzifa (2019)
Herbert B. Mayo (2008) said the investment environment nowadays is even more characterized by constant change and dynamic. There are so many choices of an asset to start in investing. Azman Anuar (2001) in Utusan Malaysia that Malaysian is not interested involved in investment compared to western people. It shows that Malaysian people did not have adequate understanding and information about the concept and the importance of investment. This is because the awareness towards investment still lacks. Thus, the main objective of this study is to study the importance of investment among student, measure the level of awareness on investment among part five students Halal Management UiTM Puncak Alam and to determine the constraint by student or young people does not want to involve in investment. This study applies a quantitative approach by using a survey as the main instrument of data collection. Fifty respondents among part five students Halal Management UiTM Puncak Alam were selected for this study. Data collected were analyzed by using Descriptive Statistic to conduct this research. In general, finding of this study shows that sources of income, scholarship, saving for future and knowledge of investment have a significant relationship to the awareness of investment among part five students Halal Management UiTM Puncak Alam.